2004
DOI: 10.1038/sj.onc.1207713
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 overexpression results in mammary gland tumorigenesis and prolonged alveolar differentiation

Abstract: MUC1 is a transmembrane mucin that was initially cloned from malignant mammary epithelial cells as a tumor antigen. More than 90% of human breast carcinomas overexpress MUC1. Numerous studies have demonstrated an interaction between MUC1 and other oncogenic proteins such as b-catenin, erbB receptors and c-Src, but a functional role for MUC1 in transformation has not been identified. We previously reported the development of transgenic mice that overexpress human MUC1 in the mouse mammary gland (MMTV-MUC1). Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 37 publications
2
120
1
1
Order By: Relevance
“…It was interesting to see that, to the exception of PLU-1/JARID1B (Lu et al, 1999), all the genes identified in our study were newly proposed as candidate cancer genes. Furthermore, MUC1 (Schroeder et al, 2004), a long known cell surface marker overexpressed in a sizeable fraction of breast tumours, and KIF14 (Corson et al, 2005), a recently proposed candidate at 1q31, presented DSs below the threshold and were excluded from our selection. Genes selected in our study belong to rather diverse functional groups, of which three appeared prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…It was interesting to see that, to the exception of PLU-1/JARID1B (Lu et al, 1999), all the genes identified in our study were newly proposed as candidate cancer genes. Furthermore, MUC1 (Schroeder et al, 2004), a long known cell surface marker overexpressed in a sizeable fraction of breast tumours, and KIF14 (Corson et al, 2005), a recently proposed candidate at 1q31, presented DSs below the threshold and were excluded from our selection. Genes selected in our study belong to rather diverse functional groups, of which three appeared prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of MAPK in association with MUC1 has been demonstrated in vitro and in the mammary glands of MMTV-MUC1 transgenic mice (Meerzaman et al, 2001;Schroeder et al, 2001). In addition, mammary gland tumors induced by overexpression of MUC1 showed increased Erk activation, and involuting MMTV-MUC1 mammary glands expressed higher levels of activated Erk2 (Schroeder et al, 2004). Erk2 has been reported to play a critical role in mediating proliferation in breast cancer cells (Flury et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic mammary glands were prepared for protein analysis as previously described (Schroeder et al, 2004).…”
Section: Protein Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that MUC1 also binds directly to p53 and regulates transcription of p53-target genes (Wei et al, 2005). Notably, overexpression of MUC1 is sufficient to induce anchorage-independent growth and tumorigenicity (Ren et al, 2002;Huang et al, 2003;Li et al, 2003b;Schroeder et al, 2004).…”
Section: Introductionmentioning
confidence: 99%